SCREENING PENYAKIT TIDAK MENULAR HEPERTENSI DENGAN PEMERIKSAAN TEKANAN DARAH - Ratna Agustiningrum; Nurhidayati, Istianna; Suciana, Fitri; Wulan Agustina, Nur; Ardiansyah (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2024)
Hypertension causes permanent disability, sudden death and very fatal consequences. To improve the quality life so that it does not cause problems in society, efforts to prevent and control hypertension need to start by increasing public awareness and chaning lifestyles towards healthier one. Hypertension is a type of non-communicable degenerative disease which is a serious problem for public health in Indonesia and the world. To improve the quality life so that it does not cause problems in society, efforts to prevent and control hypertension need to start by increasing public awareness and chaning lifestyles towards healthier one.Hypercholesterol is a condition where cholesterol levels in the body exceed normal. Hypercholesterol can increase the risk of atherosclerosis, coronary heart disease, pancreatitis (inflammation of the pancreas), diabetes mellitus, thyroid disorders, liver disease and kydney disease. In this activity, blood pressure will be checked using a sphygnomanometer, blood cholesterol will be checked using a hematology analyzer by taking blood from the brachial vein as a sample for the examination.